Integrasi Teori dan Praktik Gestalt dengan Konseling Islam - Widyawati, Lia; Nurjannah (Program Studi Bimbingan Konseling Islam Fakultas Dakwah Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
The Gestalt approach was developed by Frederick S Perls, a phenomenological existentialist therapy that emphasizes the state and condition of the here and now. Because Gestalt therapy is an experiential and humanistic approach, it works with the awareness and awareness skills of the patient. This approach is very suitable to be combined with Islamic counseling which will direct the counselee to his forrah, namely the potential to overcome the problems faced and be useful for others. The method used is literature review with the main source for obtaining data is ejournals related to the topic under study. The data obtained were analyzed to get answers in order to achieve the objectives of this study. The results of the study obtained combine the Gestal approach with effective Islamic counseling to help counselees build self-awareness and better understand the basic concept of humans being created by Allah SWT.